Automated progress monitoring in pipeline construction: a systematic review - Khan, Muhammad Hassaan Farooq; Alaloul, Wesam Salah; Musarat, Muhammad Ali; Qureshi, Abdul Hannan (Journal of Civil Engineering and Management, 2026)
Automated progress monitoring for pipeline construction is an evolving research domain among researchers which can provide effective visualisation and control of related projects. Although automation has been widely reviewed in building construction, a focused review on pipeline construction is lacking despite unique challenges and a growing need for automated monitoring. Hence, a systematic review of available methodologies and technologies was necessary to assess the achievement level of automation attained in progress monitoring practice in pipeline construction. Using the Preferred Reporting Items for Systematic Reviews and Meta-Analyses statement, relevant studies in the area were identified by using five databases: Scopus, Web of Science, ScienceDirect, American Society of Civil Engineers, and Emerald. Keyword analysis was performed by developing a keyword network, and descriptive statistics were provided. The review examines a wide range of technologies and methods for automated progress monitoring, with a focus on data acquisition tools, monitoring techniques, and their integration within unnecessary article pipeline construction scenarios. A technological process overview was developed to outline the complete monitoring workflow, while a conceptual visual representation illustrated the potential impact of tools selection and integration strategies on successful project completion, and its broader impact on sustainability and economy.